2016
DOI: 10.1080/15513815.2016.1202362
|View full text |Cite
|
Sign up to set email alerts
|

The Transition from Thin Basement Membranes to Typical Alport Syndrome Morphology in Children

Abstract: Some children with thin basement membranes (TBM) turn out to have Alport syndrome (AS). In our population of 58 children initially diagnosed with TBM, three were eventually diagnosed with AS. As a group, these three were first biopsied at a younger age, and had gross rather than microscopic hematuria. Only one had lamellations initially. Seven others had some degree of basement membrane lamellations at initial biopsy, but none of these have developed other features of AS. We concluded that at least 5% of child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Since then, the prevalence of TBMN has increased greatly and was reported to be the most common pathological finding in pediatric patients with asymptomatic hematuria [21]. Patients with TBMN generally show normal findings in LM and IF, and EM findings typically demonstrate diffuse and uniform GBM thinning; the prognosis of TBMN is good [21][22][23]. Therefore, isolated hematuria tends to be excluded among the indications for PRB in children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, the prevalence of TBMN has increased greatly and was reported to be the most common pathological finding in pediatric patients with asymptomatic hematuria [21]. Patients with TBMN generally show normal findings in LM and IF, and EM findings typically demonstrate diffuse and uniform GBM thinning; the prognosis of TBMN is good [21][22][23]. Therefore, isolated hematuria tends to be excluded among the indications for PRB in children.…”
Section: Discussionmentioning
confidence: 99%
“…Although hematuria has long been considered a benign condition related to glomerular disease, Moreno et al [ 24 ] suggested that glomerular hematuria may lead to persistent renal injury. In addition, Baek et al [ 22 ] reported that at least 5% of children initially demonstrating TBMN go on to manifest the classical electron-microscopic findings of Alport syndrome during childhood, and episodes of gross hematuria with TBMN can be a significant clue for the progression of Alport syndrome. Finally, regular follow-up of renal function in children with isolated hematuria, if possible, combined with genetic studies may be recommended [ 24 ].…”
Section: Discussionmentioning
confidence: 99%